Technology best practices - Spencer, Robert H. (John Wiley & Sons, Inc., 2003)
Technology Best Practices offers nontechnical managers a forward-thinking blueprint for implementing effective and efficient technological programs, as well as for weaving technical personnel into the managerial process.